The use of the analog wavelet filter to generate a sinusoidal signal and decompose the TEB signal into its cardiac and respiratory components in implantable cardiac pacemaker systems - Leal, Guilherme; Haddad, Sandro (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
A sinusoidal signal generator and signal decomposition filter are presented for use in systems to measure thoracic bioimpedance (TEB) in implantable cardiac pacemakers. The proposed systems use the analog wavelet filter as a base. An analysis of the proposed sinusoidal signal shows that it has a harmonic distortion rate of 1.4% and a spurious free dynamic range (SFDR) of 36.67dB. With the sinusoidal generator applied to a bioimpedance measurement system, the TEB recovery precision was 0.11Ω rms . The new TEB signal decomposer, serves for cardiac and respiratory components, using an TEB decomposer. The results show that TEB decomposer is efficient, even with variations in heart rate. Previous work indicates that the components used in the proposed systems can be implemented in circuits with ultra low energy consumption, which allows the use in implantable systems with pacemakers.